PENGEMBANGAN BUKU AJAR IPA BERBASIS LINGKUNGAN: RELEVANSINYA SEBAGAI PENGUAT KARAKTER PEDULI LINGKUNGAN - Muhammad Nuruddin; Ratih Asmarani; Claudya Zahrani Susilo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study was to develop an environment-based science textbook: its relevance as a reinforcement for the character of environmental care. The results of this study were expected to contribute to the development of primary education, especially the learning in the basic concepts of science course in PGSD Study Program. Thiagarajan (1974) reveals a 4-D development model. The data source was obtained from material analysis and was validated by experts. Then, a trial was conducted to PGSD students of Hasyim Asy'ari University in order that a quality environment-based science textbooks could be produced. Based on the descriptive analysis, it was found that the process of developing the textbook that had been carried out was in accordance with the stages. Based on inferential statistics using SPSS 26.0, namely the F test and t-test, it was obtained that the F score assuming two similar variants was 3.671 with the term of the value = 0.068. As long as the value of F> 0.05, the two variants were not different. Then, the t-test score assuming the two similar variants was 4.522 with the condition that the value is 0.000. Because the given value was <0.05, there were differences in the learning outcomes of students who used textbooks compared to students who used regular textbooks. In conclusion, this study found that the developed textbook had a good level of feasibility dan significantly influenced the students’ learning outcomes.